Effect of Basel III capital requirements on bank lending rates - Mitrová, Martina; Baran, Jaroslav; Witzany, Jiří, 1966-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2014)
The bachelor thesis studies changes in bank capital requirements brought by new regulatory framework Basel III cross-sectionally in both qualitative and quantitative manner. Theoretical knowledge is applied on utilization of an appropriate accounting model to estimate impact of changes in required capital adequacy on customer bank loan rates. The used sample consists of top bank groups of EU area for year 2013.
Vedoucí práce: Jaroslav Baran
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses